Theoretical study of BTF/TNA cocrystal： Effects of hydrostatic pressure and temperature - Chen, Peng-yuan; Zhang, Lin; Zhu, Shun-guan; Cheng, Guang-bin (Defence Technology（防务技术）, 2015)
Cocrystallization is a promising technique for the design and preparation of new explosives, and the stability of cocrystal is highly concerned by the researchers. In order to make a better understanding of the behavior of cocrystal under the extreme conditions, DFF （density functional theory） calculation is performed to investigate the effect of hydrostatic pressure on geometrical and electronic structures of the cocrystal BTF （benzotrifuroxan）/TNA （2,4,6-trinitroaniline）. When the hydrostatic pressure is applied, the lattice constants, volume, density and total energy change gradually except at the pressures of 40 GPa and 79-83 GPa. It is noteworthy that new chemical bonds form when the pressure is up to 83 GPa. The band gap of the cocrystal becomes smaller when the pressure is applied, and finally the cocrystal shows a characteristic of metal. The mechanical property of cocrystal is calculated by MD （molecular dynamics） simulation. The results show that the cocrystal has a better ductibility at low temperature, and has the best tenacity at 295 K.